2022
DOI: 10.1159/000522653
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA FOXD2-AS1 Confers Radiosensitivity to Gastric Cancer Cells via miR-1913/SETD1A Axis

Abstract: Long noncoding RNA FOXD2 adjacent opposite strand RNA1 (FOXD2-AS1) plays an oncogenic role in various cancers, including gastric cancer (GC). However, the function of FOXD2-AS1 in regulating radiosensitivity of GC cells and its underlying molecular mechanisms have not been elucidated. This study aimed to figure out the potential mechanisms of FOXD2-AS1 in regulating GC cell radiosensitivity. RT-qPCR revealed upregulation of FOXD2-AS1 in GC cells exposed to radiation. Subcellular fractionation assay was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the reductions of ACSL4, ROS, and MDA levels and increases in iron, GPX4, SOD, and GSH levels were indicative of reinforced NSCLC cell ferroptosis. In gastric cancer, the upregulation of SETD1A reverses lncRNA FOXD2‐AS1 silencing‐produced effects on cell proliferation, apoptosis, and radio‐sensitivity 30 . Taken together, HOXC‐AS3 upregulation counteracted silencing SETD1A‐exerted promotional action on NSCLC cell ferroptosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the reductions of ACSL4, ROS, and MDA levels and increases in iron, GPX4, SOD, and GSH levels were indicative of reinforced NSCLC cell ferroptosis. In gastric cancer, the upregulation of SETD1A reverses lncRNA FOXD2‐AS1 silencing‐produced effects on cell proliferation, apoptosis, and radio‐sensitivity 30 . Taken together, HOXC‐AS3 upregulation counteracted silencing SETD1A‐exerted promotional action on NSCLC cell ferroptosis.…”
Section: Discussionmentioning
confidence: 90%
“…In gastric cancer, the upregulation of SETD1A reverses lncRNA FOXD2‐AS1 silencing‐produced effects on cell proliferation, apoptosis, and radio‐sensitivity. 30 Taken together, HOXC‐AS3 upregulation counteracted silencing SETD1A‐exerted promotional action on NSCLC cell ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…FOXD2-AS1 emerges as a critical regulator in tumorigenesis. Studies have demonstrated that dysregulated FOXD2-AS1 renders gastric cancer cells more sensitive to radiation through modulation of the miR-1913/SET binding protein 1 (SETD1A) axis [10]. Suppression of FOXD2-AS1 attenuates cell proliferation, while its upregulation increased miR-31 expression and consequent dysregulation of Paired box 9 (PAX9) expression in retinoblastoma [11].…”
Section: What New Results Were Revealed?mentioning
confidence: 99%
“…The overexpression of hsa-miR-1913 was also associated with multiple forms of cancer [44][45][46][47][48][49], similar to hsa-miR-7704 [50][51][52]. However, the role of these miRNAs in HMPV infection warrants additional research.…”
Section: Discussionmentioning
confidence: 99%